Identifying an association between socio‐demographic factors and breast cancer screening adherence in a federally qualified health centre sample in the United States. A retrospective, cross‐sectional study. (18th April 2020) - Kosog, Kari; Earle, Melinda; Stellon, Ed; Nolan, Christopher; Wainwright, Mary K.; Webb, Thomas; Canar, William J.
Abstract: Federally Qualified Health Centres (FQHC) are community‐based centres in the United States, intended to fill a gap in care for underserved populations, including Medicaid patients and the homeless. Because of the Affordable Care Act, passed into law in 2010, there was a 29% increase in Medicaid enrolees nationally. One service offered at FQHCs is breast cancer screening. Breast cancer screening has been shown to have the lowest adherence levels among low‐income women and homeless women. As they serve patients with socio‐economic barriers, FQHCs are a vital resource in ensuring access to such screening. This study aimed to identity an association between socio‐demographic factors and breast cancer screening adherence in FQHC patients that included the homeless. This exploratory, cross‐sectional, retrospective study looked at encounter level data from a FQHC in a major metropolitan (Chicago, IL) area from January 1st, 2017 through December 31st, 2018. Data were collected in January of 2019. This was a convenience sample. Association was tested through bivariate chi‐square tests and multivariate logistic regression analysis, investigating the association between socio‐demographic characteristics and compliance (Yes/No) for breast cancer screening. Results showed age (55–59; 65–69) and homeless status (doubling‐up, transitional) showed a positive association with breast cancer screening, while insurance status (self‐pay) had a negative association. Age, homeless status and insurance type were significantly associated with adherence. Demographic characteristics in the homeless population can be used to identify nonadherence.